Respuesta :

Answer:

The solution set is {-1, 7}

Step-by-step explanation:

Rewrite x^2-6x=7 as x^2 - 6x                            = 7.

Identify the coefficient of the x term; it is -6.

Halve this coeff (obtaining -3)

Square this result (obtaining 9)

Add 9 to  x^2 - 6x   and then subtract 9 from the result:  x^2 - 6x  + 9 - 9

Then we have:

x^2 - 6x  + 9 - 9 = 7.  Add 9 to both sides, obtaining

x^2 - 6x  + 9       = 16

Rewrite x^2 - 6x  + 9 as the square of a binomial:  (x - 3)^2

Then we have

(x - 3)^2 = 16

Taking the square root of both sides, we get

x - 3 = ±4, so that:  x = 3 + 4 = 7, and x = 3 - 4 = -1.

The solution set is {-1, 7}.

Answer:

To complete the square x^2-6x=7

We take the coefficient of X which is -6

     divide it by 2  -3

     square that number 9

     then add it to both sides of the equation.

x^2 -6x + 9 = 16

(x -3) * (x -3) = 16

We take the square root of both sides:

a) x-3 = 4

b) x-3 = -4

Therefore, x = 7 and x = -1

Step-by-step explanation:

ACCESS MORE